2010
DOI: 10.1111/j.1552-6569.2010.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Due to Lyme Neuroborreliosis: Changes in Vessel Wall Contrast Enhancement

Abstract: Gadolinium-enhanced MRI provided additional information facilitating the diagnosis of vasculitis in a child with Lyme neuroborreliosis and stroke. The location of vessel wall enhancement was correlated with the topography of the acute infarct, and the lack of vessel lumen obstruction supported the diagnosis of vasculitis rather than any other cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The occurrence of meningeal vasculitis with multiple stenosis of large cerebral arteries with secondary cerebral infarcts in the territories of middle and posterior cerebral arteries, basilar and anterior spinal arteries have been repeatedly reported [52, 53, 76, 85, 89, 102, 104, 105, 107-124]. In a pathologically confirmed case [47, 106] the typical meningovascular alterations of Heubner’s arteritis and chronic meningitis were documented (Fig.…”
Section: Lyme Diseasementioning
confidence: 87%
See 2 more Smart Citations
“…The occurrence of meningeal vasculitis with multiple stenosis of large cerebral arteries with secondary cerebral infarcts in the territories of middle and posterior cerebral arteries, basilar and anterior spinal arteries have been repeatedly reported [52, 53, 76, 85, 89, 102, 104, 105, 107-124]. In a pathologically confirmed case [47, 106] the typical meningovascular alterations of Heubner’s arteritis and chronic meningitis were documented (Fig.…”
Section: Lyme Diseasementioning
confidence: 87%
“…It is also noteworthy, that regressive evolution of cerebral infarct in meningovascular Lyme neuroborreliosis and improvement or disappearance of neuropsychiatric symptoms in Lyme encephalitis following antibiotic treatment were reported by many authors [42, 52, 53, 59, 82, 85, 89, 90, 102, 113-115, 120, 122, 128, 140-142, 158, 159]. …”
Section: Lyme Diseasementioning
confidence: 91%
See 1 more Smart Citation
“…56 Several case reports, exclusively from Europe, have demonstrated cerebral infarction due to vasculitis associ ated with Lyme disease. 46 preceding complaints of headache or recurrent episodes of neurological deficits, as well as those with multiple ischaemic lesions (especially of the posterior circulation), might also have experienced stroke related to Lyme neuroborreliosis. 47,48 Notably, the long-term outcomes of patients with neuroborreliosis-associated stroke seem to be worse than those of typical patients with stroke.…”
Section: Manifestations and Diagnosismentioning
confidence: 97%
“…[46][47][48] In Europe, clinical studies have reported signs of polyneuropathy in 40-60% of patients who present with a pathognomonic late cutaneous manifestation of Lyme disease, acrodermatitis chronica atrophicans (ACA). [49][50][51] The ACA-associated polyneuropathy is asymmetric and predominantly sensory, and usually follows the skin lesion.…”
Section: Manifestations and Diagnosismentioning
confidence: 99%